Experimental investigation of stress unloading effects on rock damage and confining pressure-dependent crack initiation stress of porous sandstone under true triaxial stress environments - Qingsheng Bai; Max Friedel; Heinz Konietzky (Rock Mechanics Bulletin, 2024)
This study investigates the impact of intermediate (σ2) and minimum (σ3) principal stress unloading on damage behavior and the confining pressure influence on crack initiation stress (σci) in true triaxial stress conditions, utilizing large-scale cubic samples. Two distinct true triaxial tests were executed, examining the effects of confining stress (σ2 and σ3) unloading on porous sandstone damage and the correlation between confining stress and σci. Acoustic emission (AE) parameters, signal characteristics, and wave velocity variations were utilized to elucidate cracking mechanisms and damage development in the samples. Unloading tests reveal consistent velocities in three orthogonal directions (V11, V22, and V33) during the initial two unloading stages. In the subsequent three stages, confining stress unloading leads to a decrease in wave velocity in the corresponding direction, while velocities in the other two directions remain nearly constant. Notably, σ2 unloading generates higher amplitude AE signals compared to σ3 unloading, with over 70% of the micro-cracks categorized as tensile. In the incremental loading tests, σci is found to be contingent on confining pressure, with σ2 playing a crucial role. During σ1 loading, V33 decreases, indicating additional crack formation; conversely, σ3 loading results in V33 increase, signifying the continuous closure of existing cracks. Limitations of the experiments are summarized and prospects in this domain are outlined.